2016
DOI: 10.1159/000445604
|View full text |Cite
|
Sign up to set email alerts
|

Amlodipine and Atorvastatin Improved Hypertensive Cardiac Remodeling through Regulation of MMPs/TIMPs in SHR Rats

Abstract: Background: MMPs/TIMPs system is well known to play important roles in pressure overload-induced cardiac remodeling, and Amlodipine and Atorvastatin have been showed to exert favourable protective effects on cardiovascular disease, however, it is not clear whether Amlodipine and Atorvastatin can improve hypertensive cardiac remodeling and whether the MMPs/TIMPs system is involved. The present study aims to answer these questions. Methods: 36 weeks old male spontaneous hypertension (SHR) rats were randomly divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
0
12
0
1
Order By: Relevance
“…As early as 2001 [13], Takemoto et.al raised that statins could be used as antioxidant therapy to prevent cardiac myocyte hypertrophy. A latest report [14] also showed that Ato helped improve hypertensive cardiac remodeling by Regulating MMPs/TIMPs in SHR Rats. Similarly, a study [4] of radiation-induced cardiac fibrosis revealed an obvious therapeutic effect of Ato, which also partly supports our findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As early as 2001 [13], Takemoto et.al raised that statins could be used as antioxidant therapy to prevent cardiac myocyte hypertrophy. A latest report [14] also showed that Ato helped improve hypertensive cardiac remodeling by Regulating MMPs/TIMPs in SHR Rats. Similarly, a study [4] of radiation-induced cardiac fibrosis revealed an obvious therapeutic effect of Ato, which also partly supports our findings.…”
Section: Discussionmentioning
confidence: 99%
“…The SHR group (n=8) and WKY group (n=8) received 1 mL distilled water/day by gavage. The Ato-treated SHR group (n=8) received a low dosage of 10 mg/kg/day [12] i.g. The Ato-treated SHR group (n=8) received a medium dosage of 25 mg/kg/day i.g.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies showed that MMPs, specifically MMP-2 and MMP-9, were activated rapidly following vascular injury [36-38] and played an important role in disrupting the ECM in VSMCs [37, 39]. Degradation of the ECM promoted VSMC migration from the media of arterial walls to the intimal space, where VSMCs secreted more ECM products, progressively resulting in restenosis and neointima formation [40, 41].…”
Section: Discussionmentioning
confidence: 99%
“…TIMP is a type of MMP inhibitor, and MMP/TIMP imbalance can cause abnormal extracardiomyocyte collagen accumulation, which leads to ventricular stiffening and myocardial fibrosis and prevents myocardial relaxation and contraction. TIMPs can block MMPs from binding to their substrates and inhibit their activity, which subsequently delays the progression of ventricular remodeling (12,13). TIMP-3 is a member of the TIMP family and is a specific non-soluble protein that inhibits MMP activity.…”
Section: Discussionmentioning
confidence: 99%